Promosi Kesehatan Skrining Dan Kie Diabetes Melitus Melalui Media Leaflet Untuk Meningkatan Pengetahuan Dikelurahan Batu Urip Lubuklinggau Utara II - Miftah risky umami; Novita Agustina; Eka Agustiana Sari; Eka Apriani; Nia Agustinah; Danur Azissah (Jurnal Pengabdian Kepada Masyarakat, 2024)
Diabetes mellitus is a chronic metabolic disorder characterized by blood sugar levels that exceed normal limits (hyperglycemia). Knowledge is a very important factor in the actions of people with diabetes mellitus, behavior that is based on knowledge will be easier to implement than that which is not based on knowledge. The aim of this screening and counseling is to increase knowledge about diabetes in the surrounding community so that people know how important it is to maintain health. The methods used in this activity are action research methods and participatory activity programs with the community. The results of outreach activities about diabetes mellitus to residents in RT 2 Batu Urip Village were that the average pre-test knowledge of residents about diabetes mellitus before being given counseling was 60% in the poor category. Then the average post-test knowledge of residents after counseling on diabetes mellitus was 60% in the good category. From the results of the community service carried out, it can be concluded that there are still many people who do not realize the importance of maintaining lifestyle and habits to avoid diabetes and carrying out health laboratory examinations at the nearest health center so that many people still suffer from diabetes.